Effect of homogenised and pasteurised versus native cows' milk on gastrointestinal symptoms, intestinal pressure and postprandial lipid metabolism - Nuora A; Tupasela T; Tahvonen R; Rokka S; Marnila P; Viitanen M; Makela P; Pohjankukka J; Pahikkala T; Yang BR; Kallio H; Linderborg K (ELSEVIER SCI LTD, 2022)
Some people experience gastrointestinal symptoms related to cow's milk consumption even if neither lactose intolerance nor cow's milk allergy can be diagnosed. To investigate whether milk homogenization could cause gastrointestinal problems, homogenized and pasteurized milk and native milk were served to eleven volunteers who reported such sensitivity in a random order together with an ingestible pressure measuring capsule. Postprandial lipemia did not differ between the two milk types, but significant differences were found in the postprandial plasma fatty acid composition. No significant difference was found in the amount of gastrointestinal symptoms or in the intestinal pressure after the consumption of native and processed milk. However, the obtained results on pressure in the large intestine (P = 0.068) as well as reported symptoms (P = 0.103) suggest that further studies in this area are needed with a bigger subject group and with longer exposure times to differently processed milk types. (C) 2017 Elsevier Ltd. All rights reserved.